Lemmel Syndrome: A Case Study and Literature Review - Mazzini, Manuel Bernardo Balladares; Salazar, Manuel Francisco Balladares; Sánchez, Janet Paola Emén; Escudero, Marcela María Veloz; amaya, Josefina Elizabeth Ramírez; Acuña, Luvia Tamara García (Journal of Ecohumanism, 2025)
Objective. The research objective was to describe the current state of knowledge about Lemmel Syndrome. Methodology. This research focused on an exhaustive literature review and a clinical case report of Lemmel Syndrome. The literature review was conducted using databases such as PubMed, EMBASE, and other relevant sources, including MeSH terms, DeCS terms, and specific keywords related to the study dimensions. The clinical case involved a 58-year-old female patient who presented to Hospital Luis Vernaza in Guayaquil, Ecuador, with an anatomical history of a juxtapapillary diverticulum. The patient presented with a 12-hour history of diffuse and intense abdominal pain, unresponsive to oral analgesics, accompanied by nausea, vomiting, fever (38°C), and general malaise, raising suspicion for Lemmel Syndrome. Results and Discussion. Lemmel Syndrome, while infrequent, should be considered as a differential diagnosis in patients with gastrointestinal symptoms. The pathophysiology of this condition, related to compression of the common bile duct by a juxtapapillary diverticulum, justifies the central role of ERCP as the diagnostic and therapeutic tool of choice. While conservative management and ERCP are often sufficient to resolve biliary obstruction, surgery may be necessary in cases of complications or lack of response to endoscopic treatment. Advances in endoscopic techniques and materials suggest a promising future for individualized and timely treatment of this and similar pathologies.